2006
DOI: 10.1197/j.aem.2005.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomographic Angiography for the Evaluation of Aneurysmal Subarachnoid Hemorrhage

Abstract: In this pilot study, CTA was found to be useful in the detection of cerebral aneurysms and may be useful in the diagnosis of aneurysmal SAH. A larger multicenter study would be useful to confirm these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 38 publications
(58 reference statements)
1
25
0
Order By: Relevance
“…22 A single prospective study of patients with clinical presentations suggestive of SAH has been performed directly comparing CT/CTA with CT/ LP in 106 patients. 6 Based on strict criteria, 2 patients had positive results of LP, and in both cases aneurysms were revealed by CTA and confirmed by DSA. In 100 patients, the results of both LP and CTA were negative, and it is unknown if any of these patients suffered subsequent bleeds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 A single prospective study of patients with clinical presentations suggestive of SAH has been performed directly comparing CT/CTA with CT/ LP in 106 patients. 6 Based on strict criteria, 2 patients had positive results of LP, and in both cases aneurysms were revealed by CTA and confirmed by DSA. In 100 patients, the results of both LP and CTA were negative, and it is unknown if any of these patients suffered subsequent bleeds.…”
Section: Discussionmentioning
confidence: 99%
“…2,18,27 Multidetector CTA is considered to be excellent in the detection of aneurysms 1,9,13,34 and has been estimated to have a sensitivity of 99.4% in detecting ruptured aneurysms compared with intraoperative findings. 24 CTA can sometimes detect aneurysms missed by CT/LP 6 and digital subtraction angiography (DSA). 3 We hypothesized that acute headache patients with negative findings on noncontrast head CT and an LP positive for CSF RBCs who have no aneurysm or neurovascular lesion on cerebrovascular imaging are at low risk for subsequent catastrophic SAH.…”
mentioning
confidence: 99%
“…The only study on ED patients with headache who underwent CTA showed an aneurysm prevalence of 5% (5 ⁄ 106), with 3% (3 ⁄ 106) being culprit lesions, one being potentially symptomatic (1 ⁄ 106), and one being most likely incidental (1 ⁄ 106). 21 The clinical utility of the CT ⁄ CTA approach may be determined by the true prevalence of these nonbleeding aneurysms and the implications for patient management and follow-up. Discovering ''incidental'' aneurysms may subject the patient to additional risk from subsequent testing and interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the current literature, the prevalence is between 3% and 16% (Table 1). 1,[19][20][21][22] We have conservatively estimated the prevalence of SAH in an ED patient complaining of an acute-onset headache with an intact neurologic exam as 15%. Although the actual prevalence may be lower, assuming a higher prevalence in a probability model will maximize the number of potential missed cases and reveal weaknesses in the model.…”
Section: Sah Prevalencementioning
confidence: 99%
“…The clinical examination findings were not reported in any patients. One of the patients with an middle cerebral artery aneurysm refused surgical treatment and had no reported adverse events in a 1-year follow-up, 10 suggesting that the aneurysm was incidental. In fact, the number of aneurysms detected is exactly what one would expect in an unselected population.…”
mentioning
confidence: 99%